Preparation method and application of photocatalyst for low concentration CO2 reduction
The Hv-Co-MHOF photocatalyst was prepared by co-precipitation method and NaBH4 reduction etching, which solved the problem of low reduction efficiency of CO2 at low concentration, and achieved efficient CO2 conversion to CH4, with excellent catalytic performance and low cost preparation characteristics.
Patent Information
- Application Number
- CN202410905904.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-08
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-07-08
AI Technical Summary
The prior art is difficult to effectively catalyze the reduction of low-concentration CO2, especially when the CO2 concentration in industrial waste gas is low, the performance of the catalyst is not ideal, and there are problems of large energy consumption and increased carbon emissions.
Co-MHOF precursor was prepared by co-precipitation method, and reduced etching was performed using NaBH4 reducing agent to form oxygen vacancies and modulate the valence ratio of cobalt metal, and prepare Hv-Co-MHOF photocatalyst. This method can improve the CO2 conversion efficiency and CH4 product selectivity of the catalyst.
It realizes efficient catalytic conversion of low concentration CO2 under simulated sunlight, significantly improves CO2 conversion efficiency and CH4 product selectivity, and is simple in preparation method and low in cost, suitable for mass production.
Smart Images

Figure CN118847227B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalyst preparation, and in particular relates to a preparation method and application of a photocatalyst for low-concentration CO2 reduction. Background Art
[0002] In recent years, excessive consumption of fossil fuels has led to a severe energy crisis and greenhouse gas effects, primarily carbon dioxide, which have seriously affected the effective circulation of carbon resources in nature. Therefore, it is necessary to explore efficient and low-cost CO2 treatment methods to maintain carbon balance. To this end, researchers have designed and developed a variety of CO2 capture and storage technologies, and have developed thermochemical, electrochemical, photochemical, photothermochemical and other methods to effectively catalyze the conversion of CO2 into high-value-added chemicals or fuels. Among them, photocatalytic CO2 reduction technology has the advantages of being green, environmentally friendly and having a mild process, and is regarded as one of the ways to mitigate global warming and achieve effective recycling of carbon resources.
[0003] Photocatalytic CO2 reduction refers to the process in which semiconductor photocatalysts absorb incident light with energy greater than their band gap width and generate electrons and holes, thereby converting CO2 and H2O into high-value-added chemicals. In this process, the high dissociation energy of CO2 molecules and the kinetic characteristics of multi-electron transfer-proton coupling seriously restrict the improvement of catalytic efficiency and selectivity. To this end, researchers have developed and designed a variety of catalysts and modified them to improve the performance of CO2 reduction photocatalysts, including: (1) regulation of photocatalyst morphology and size, such as the construction of cavity structure and nano-thin layer structure; (2) construction of surface defects, such as the introduction of oxygen and sulfur vacancies; (3) heterostructure construction; (4) crystal surface regulation. Based on the above strategies, the performance of the catalyst can be significantly improved, including: CO2 adsorption capacity, charge separation ability, visible light response range, etc.
[0004] Despite this, research in this field has achieved high catalytic activity in a pure CO2 atmosphere, and there are relatively few reports on the catalytic conversion of low-concentration CO2 and the results are not ideal. In particular, the concentration of CO2 in actual industrial waste gas is low (5-30%), and accounts for 60-70% of anthropogenic CO2 emissions. If the low-concentration CO2 is purified and concentrated before reduction, it will not only consume huge energy, but also lead to a further increase in carbon emissions. Therefore, the design and development of a photocatalytic system that effectively adsorbs low-concentration CO2 and efficiently converts it into high-value chemicals is of great significance to the realization of carbon neutrality goals. It is worth noting that photocatalysts that directly reduce low-concentration CO2 usually need to meet higher requirements, such as good CO2 enrichment ability, high catalytic activity at low CO2 concentrations, and resistance to complex gas components (such as O2, SO x 、NO x) poisoning, stable structure and low cost. In the past five years, researchers have developed various photocatalysts for the reduction of low-concentration CO2, including metal organic frameworks, covalent organic frameworks, metal oxides, single-atom catalysts, etc. In addition, people have also adopted various strategies to further improve the performance of low-concentration CO2 photoreduction, mainly by constructing surface alkaline sites, developing and designing porous materials, introducing ionic liquids, etc., trying to improve the enrichment and adsorption capacity of CO2, thereby improving the low-concentration CO2 photoreduction catalytic performance. However, the photocatalytic reduction effect of existing catalysts on low-concentration CO2 is not ideal, and the development of efficient photocatalysts for low-concentration CO2 reduction is still the focus of research for those skilled in the art. Summary of the Invention
[0005] The purpose of the present invention is to provide a method for preparing a photocatalyst for low-concentration CO2 reduction, and to use the prepared photocatalyst to simulate the low-concentration CO2 catalytic conversion reaction under sunlight, showing excellent CO2 conversion efficiency and CH4 product selectivity.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention: A method for preparing a photocatalyst for low-concentration CO2 reduction, comprising the following steps:
[0008] A Co-MHOF (cobalt metal hydroxide organic framework) precursor is prepared by a coprecipitation method using a cobalt source, an intercalation anion and an alkali source as raw materials; the Co-MHOF precursor is reduction-etched by a reducing agent to obtain the photocatalyst (Hv-Co-MHOF photocatalyst).
[0009] By reducing etching, oxygen vacancies are formed in the Co-MHOF precursor and the cobalt metal valence state (Co 3+ and Co 2+ The essence of the above technical solution is to use Co-MHOF as a template, form oxygen vacancies by using different concentrations of NaBH4 reduction etching, and adjust the active metal valence ratio (Co 3+ and Co 2+ By adjusting the oxygen vacancy concentration and the ratio of active metal valence states in the catalyst, the activity of the metal catalytic sites can be changed.
[0010] Furthermore, the cobalt source is a cobalt inorganic acid salt, the alkali source is sodium hydroxide, and the intercalation anion is a salicylate ion. That is, the Co-MHOF precursor is prepared by a coprecipitation method using sodium hydroxide as the alkali source, the cobalt inorganic acid salt as the precursor, and the salicylate ion as the intercalation anion.
[0011] Furthermore, the step of preparing a cobalt metal hydroxide organic framework precursor by a coprecipitation method includes: adding a cobalt inorganic acid salt solution (referred to as solution one) to a salicylate ion solution (referred to as solution two) under stirring conditions to obtain a mixed solution (referred to as solution three); adding a sodium hydroxide solution dropwise to the mixed solution, heating and aging after the addition is completed, and after the aging is completed, centrifuging, washing, and drying to obtain the Co-MHOF precursor.
[0012] Furthermore, the inorganic acid salt of cobalt is cobalt nitrate hexahydrate.
[0013] Furthermore, the concentration of the cobalt inorganic acid salt solution is 0.01-1 mol·L -1 The concentration of the salicylate ion solution is 0.01-0.5 mol·L -1 .
[0014] Furthermore, the concentration of the sodium hydroxide solution is 0.05-0.5 mol·L -1 .
[0015] Furthermore, the preparation method of the inorganic cobalt salt solution is: dissolving an inorganic cobalt salt in water to obtain the inorganic cobalt salt solution; the preparation method of the salicylate ion solution is: dissolving salicylate in water to obtain the salicylate ion solution; the preparation method of the sodium hydroxide solution is: dissolving sodium hydroxide in water to obtain a sodium hydroxide solution.
[0016] Furthermore, the volume ratio of the cobalt inorganic acid salt solution to the salicylate ion solution is 2:3.
[0017] Furthermore, during the process of adding the sodium hydroxide solution dropwise to the mixed solution, the dropping speed is controlled so that the pH of the solution system is maintained in the range of 7.0-9.0.
[0018] Furthermore, the aging temperature is 80-95° C. and the aging time is 16-24 hours.
[0019] Furthermore, the washing is performed with deionized water until the mixture becomes neutral; and the drying temperature is 60° C. and the drying time is 12 hours.
[0020] Furthermore, the reduction etching of the Co-MHOF precursor using a reducing agent includes: mixing the Co-MHOF precursor, the reducing agent and water to obtain a mixed solution, stirring and performing reduction etching, and after the reduction etching is completed, centrifuging, washing and drying to obtain the photocatalyst.
[0021] Furthermore, the reducing agent is sodium borohydride (NaBH4); the concentration of the reducing agent in the mixed solution is 0.01-1 mol·L -1(ie, the ratio of reducing agent to water is 0.01-1 mol:1 L); the reduction etching time is 10-60 min.
[0022] During the reduction etching process, the oxygen vacancy concentration and the active metal valence state ratio can be controlled by regulating the concentration of NaBH4 in the mixed solution and the reduction time, and a series of Hv-Co-MHOF photocatalysts containing different oxygen vacancy concentrations and different active metal valence state ratios can be prepared.
[0023] Furthermore, the usage ratio of the Co-MHOF precursor and water is 0.1 g:40 mL.
[0024] Furthermore, the washing is performed with deionized water until the mixture becomes neutral; and the drying temperature is 60° C. and the drying time is 12 hours.
[0025] The second technical solution of the present invention: a photocatalyst for low-concentration CO2 reduction prepared according to the above preparation method.
[0026] The third technical solution of the present invention: an application of the above-mentioned photocatalyst in the photocatalytic reduction of low-concentration CO2 to produce methane, wherein the volume concentration of the low-concentration CO2 is 2-50%.
[0027] Furthermore, the photocatalytic reduction is carried out under simulated sunlight, that is, the photocatalyst is used to catalytically reduce low-concentration CO2 to CH4 under simulated sunlight.
[0028] Furthermore, the light source for the photocatalytic reduction is a 300W xenon lamp equipped with a total reflection plate and an AM1.5 G filter to simulate the solar spectrum.
[0029] Furthermore, the photocatalytic reduction is carried out in a volume of 50 cm 3 was carried out in a photocatalytic reactor.
[0030] Inventive Concept: The present invention first prepares a Co-MHOF (cobalt metal hydroxide organic framework) precursor via a coprecipitation method using a cobalt source, intercalation anions, and an alkali source as raw materials. MHOF is a uniquely structured metal-organic framework (MOF) that combines the porous properties of MOF materials with the excellent catalytic activity of metal hydroxide (LDH) materials, effectively enriching low-concentration CO2 atmospheres. The interlayer organic anions are tightly connected by π-π conjugation, giving the material excellent structural stability, separation and migration capabilities of photogenerated electrons, and good visible light absorption. The Co-MHOF precursor is then subjected to reduction etching using the reducing agent sodium borohydride, forming oxygen vacancies in the Co-MHOF precursor and modulating the cobalt metal valence ratio. Compared to other methods, the NaBH4 reduction method can effectively control the oxygen vacancy concentration and active metal valence ratio, thereby modulating the activity of the active metal sites and improving photocatalytic activity. The photocatalyst prepared by the present invention was used to simulate the catalytic conversion of low-concentration CO2 under sunlight, demonstrating excellent CO2 conversion efficiency and CH4 product selectivity.
[0031] The present invention discloses the following technical effects:
[0032] The present invention first prepares a Co-MHOF (cobalt metal hydroxide organic framework) precursor by a co-precipitation method, and then uses the Co-MHOF precursor as a template, adopts reducing agents of different concentrations to reduce and etch oxygen vacancies, and adjusts the ratio of active metal valence states to obtain a Hv-Co-MHOF photocatalyst. The Co-MHOF precursor has both the porous characteristics of MOF materials and the good catalytic activity of metal hydroxide (LDH) materials, and itself has good catalytic performance. Compared with the Co-MHOF precursor, in terms of photocatalytic performance, the introduction of oxygen vacancies and the change of the ratio of active metal valence states after reduction etching adjust the electronic structure of the catalyst and reduce the band gap width, thereby accelerating the separation efficiency of photogenerated charges and holes, improving the utilization rate of photogenerated carriers, and significantly improving the activity and selectivity of photocatalytic CO2 to CH4 conversion; in terms of production application, the preparation method of the present invention is simple and novel, the synthesis cost is low, it is easy to mass produce, and it has good application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0034] Figure 1 This is the X-ray powder diffraction pattern of the Co-MHOF photocatalyst in Example 1.
[0035] Figure 2 This is the X-ray powder diffraction pattern of the Hv-Co-MHOF-a photocatalyst in Example 2.
[0036] Figure 3 This is the X-ray powder diffraction pattern of the Hv-Co-MHOF-b photocatalyst in Example 3.
[0037] Figure 4 This is a scanning electron microscope image of the Co-MHOF photocatalyst in Example 1.
[0038] Figure 5 This is a scanning electron microscope image of the Hv-Co-MHOF-a photocatalyst in Example 2.
[0039] Figure 6 This is a scanning electron microscope image of the Hv-Co-MHOF-b photocatalyst in Example 3.
[0040] Figure 7 This is a high-resolution transmission electron microscopy image of the Hv-Co-MHOF-a photocatalyst in Example 2.
[0041] Figure 8 This is the surface element distribution diagram of the Hv-Co-MHOF-a photocatalyst in Example 2.
[0042] Figure 9 C1s X-ray photoelectron spectra of the Co-MHOF photocatalyst in Example 1, the Hv-Co-MHOF-a photocatalyst in Example 2, and the Hv-Co-MHOF-b photocatalyst in Example 3.
[0043] Figure 10 1s X-ray photoelectron spectra of the Co-MHOF photocatalyst in Example 1, the Hv-Co-MHOF-a photocatalyst in Example 2, and the Hv-Co-MHOF-b photocatalyst in Example 3.
[0044] Figure 11 2p X-ray photoelectron spectra of the Co-MHOF photocatalyst in Example 1, the Hv-Co-MHOF-a photocatalyst in Example 2, and the Hv-Co-MHOF-b photocatalyst in Example 3.
[0045] Figure 12 This is a diagram showing the catalytic performance of the Co-MHOF photocatalyst in Example 1 for catalytic reduction of low-concentration carbon dioxide to methane under simulated solar spectrum conditions.
[0046] Figure 13This is a diagram showing the catalytic performance of the Hv-Co-MHOF-a photocatalyst in Example 2 for catalytic reduction of low-concentration carbon dioxide to methane under simulated solar spectrum conditions.
[0047] Figure 14 This is a diagram showing the catalytic performance of the Hv-Co-MHOF-b photocatalyst in Example 3 for catalytic reduction of low-concentration carbon dioxide to methane under simulated solar spectrum conditions.
[0048] Figure 15 Graph showing the selectivity of the Co-MHOF photocatalyst in Example 1, the Hv-Co-MHOF-a photocatalyst in Example 2, and the Hv-Co-MHOF-b photocatalyst in Example 3 for catalyzing the reduction of low-concentration carbon dioxide to methane under simulated solar light conditions. DETAILED DESCRIPTION
[0049] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0050] It should be understood that the terms described herein are intended only to describe particular embodiments and are not intended to limit the present invention. In addition, for numerical ranges herein, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value within any stated value or stated range, and each smaller range between any other stated value or intermediate value within the stated range, is also encompassed within the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded within the scope.
[0051] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of any conflict with any incorporated document, the contents of this specification shall prevail.
[0052] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments described herein without departing from the scope or spirit of the invention. Other embodiments will be apparent to those skilled in the art from the description of the invention. The description and examples are intended to be illustrative only.
[0053] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0054] Unless otherwise specified, the "room temperature" in the present invention is 25°C.
[0055] The raw materials used in the following examples and comparative examples of the present invention are all commercially available products.
[0056] Example 1
[0057] Preparation of Co-MHOF photocatalyst:
[0058] At room temperature, 2.91 g (0.01 mol) of cobalt nitrate hexahydrate was dissolved in 50 mL of deionized water and stirred to form solution 1. 3.20 g of sodium salicylate (0.02 mol) was dissolved in 75 mL of deionized water and stirred to form solution 2. Solution 1 was quickly added to solution 2 under magnetic stirring at 450 r / min to obtain solution 3. 1 mol·L -1 The sodium hydroxide solution was slowly added dropwise to Solution 3, controlling the addition rate to maintain a pH between 7.8 and 8.2. After the addition was complete, the solution was aged at 95°C for 24 hours. The precipitate was centrifuged and washed to neutrality, then dried at 60°C for 12 hours to produce the Co-MHOF precursor.
[0059] Example 2
[0060] Preparation of Hv-Co-MHOF-a photocatalyst:
[0061] 0.1 g of the Co-MHOF precursor prepared in Example 1 was weighed and dissolved in 40 mL of deionized water. 454 mg (0.012 mol) of sodium borohydride was added thereto under magnetic stirring to obtain a mixed solution (wherein the concentration of sodium borohydride was 0.3 mol·L -1 ), and then stirred for 30 min, and the precipitate was centrifuged and washed until neutral, and dried in a vacuum drying oven at 60 ° C for 12 h to obtain Hv-Co-MHOF-a.
[0062] Example 3
[0063] Preparation of Hv-Co-MHOF-b photocatalyst:
[0064] 0.1 g of the Co-MHOF precursor prepared in Example 1 was weighed and dissolved in 40 mL of deionized water. 1.5 g (0.04 mol) of sodium borohydride was added thereto under magnetic stirring to obtain a mixed solution (wherein the concentration of sodium borohydride was 1 mol·L -1 ), and then stirred for 30 min, and the precipitate was centrifuged and washed until neutral, and dried in a vacuum drying oven at 60 ° C for 12 h to obtain Hv-Co-MHOF-b.
[0065] Test Example 1
[0066] Structural morphology characterization of the photocatalytic materials prepared in Examples 1-3:
[0067] Figure 1 is the X-ray powder diffraction pattern of the Co-MHOF photocatalyst in Example 1; Figure 4 This is a scanning electron microscope image of Co-MHOF in Example 1. It can be seen that the material has a high degree of crystallinity ( Figure 1 ), has a layered structure and presents a long strip-like structure ( Figure 4 ), which is conducive to exposing more active sites.
[0068] Figure 2 is the X-ray powder diffraction pattern of the Hv-Co-MHOF-a photocatalyst in Example 2; Figure 5 is a scanning electron microscope image of the Hv-Co-MHOF-a photocatalyst in Example 2; Figure 7 is a high-resolution transmission electron microscopy image of the Hv-Co-MHOF-a photocatalyst in Example 2; Figure 8 The surface element distribution diagram of the Hv-Co-MHOF-a photocatalyst in Example 2. It can be seen that when the amount of sodium borohydride reducing agent is small, the crystallinity of the material is slightly reduced ( Figure 2 ), but still retains a good layered structure and thin layered banded structure ( Figure 5 and Figure 7 ), Co, C, and O elements are evenly distributed on the catalyst surface ( Figure 8 ).
[0069] Figure 3 is the X-ray powder diffraction pattern of the Hv-Co-MHOF-b photocatalyst in Example 3; Figure 6 This is a scanning electron microscope image of the Hv-Co-MHOF-b photocatalyst in Example 3. It can be seen that when the amount of sodium borohydride reducing agent is large, the crystallinity of the material is significantly reduced ( Figure 3 ), the layered structure and the banded structure are destroyed to a certain extent ( Figure 6 ).
[0070] Test Example 2
[0071] Electronic structure characterization of the photocatalytic materials prepared in Examples 1-3:
[0072] In order to explore the effect of the amount of sodium borohydride reducing agent on the electronic structure and chemical valence state of the catalyst, the present invention conducted X-ray photoelectron spectroscopy characterization. Figure 9The following are the C1s X-ray photoelectron spectra of the Co-MHOF photocatalyst in Example 1, the Hv-Co-MHOF-a photocatalyst in Example 2, and the Hv-Co-MHOF-b photocatalyst in Example 3. It can be seen that as the amount of NaBH4 reducing agent increases, the characteristic peak at the binding energy of 289.5 eV attributed to OC=O gradually decreases, indicating that the coordination structure between the interlayer anions and the layer cations of the catalyst is gradually destroyed, and the layered structure gradually collapses.
[0073] Figure 10 The O1s X-ray photoelectron spectra of the Co-MHOF photocatalyst in Example 1, the Hv-Co-MHOF-a photocatalyst in Example 2, and the Hv-Co-MHOF-b photocatalyst in Example 3 are shown. The characteristic peaks at the binding energies of 531.3 eV, 532.7 eV, and 535.4 eV are respectively attributed to O α , O β , O γ (O α : lattice oxygen; O β : oxygen vacancy or adsorbed oxygen; O γ :OC=O). It can be seen that as the amount of NaBH4 reducing agent increases, O γ The characteristic peak first decreases and then disappears. β The proportion gradually increases, indicating that the NaBH4 reduction method creates oxygen vacancies, which destroys the coordination structure between the catalyst interlayer anions and the layer cations, and then the structure collapses, which is consistent with the C1s XPS results.
[0074] Figure 11 The Co 2p X-ray photoelectron spectra of the Co-MHOF photocatalyst in Example 1, the Hv-Co-MHOF-a photocatalyst in Example 2, and the Hv-Co-MHOF-b photocatalyst in Example 3 are shown. The characteristic peaks at the binding energies of 781.2 eV and 785.6 eV are respectively attributed to Co 3+ and Co 2+ , and with the increase of the amount of NaBH4 reducing agent, Co 3+ The proportion gradually increases. This shows that the NaBH4 reduction method to create oxygen vacancies can effectively control the proportion of active metal ions, thereby adjusting the CO2 photoreduction activity.
[0075] In summary, by adjusting the amount of NaBH4 reducing agent, the oxygen vacancy concentration can be precisely controlled, and the ratio of active metal valence states can be changed to regulate the photocatalytic activity of the material.
[0076] Effect Example 1
[0077] The photocatalyst prepared in Examples 1-3 was tested for its performance in reducing low-concentration CO2:
[0078] Test method: Weigh 20 mg of photocatalyst into 100 μL of deionized water and spread it on a 50 cm 3 In an offline photocatalytic reactor, a 10% CO₂ (CO₂ / Ar = 1:9) reaction atmosphere was used at atmospheric pressure, using a 300W xenon lamp equipped with a total reflector and an AM1.5G filter to simulate the solar spectrum. Samples were taken every hour using a gas-tight needle, and the gas product composition was analyzed by gas chromatography. The reaction was terminated after 5 hours, and the selectivity and yield of CO₂ reduction to methane were measured.
[0079] Figure 12 、 13 14 are the catalytic performance diagrams of the catalytic reduction of low-concentration carbon dioxide to methane by the Co-MHOF photocatalyst in Example 1, the Hv-Co-MHOF-a photocatalyst in Example 2, and the Hv-Co-MHOF-b photocatalyst in Example 3, respectively. It can be seen that with the increase in the amount of sodium borohydride reducing agent, the catalytic performance presents a volcano-shaped curve, and the Hv-Co-MHOF-a photocatalyst has the best methane production rate. This is mainly because with the increase in the amount of sodium borohydride reducing agent introduced, the oxygen vacancy concentration gradually increases, and the Co 3+ The proportion of reducing agent gradually increases, so that it has the best catalytic activity. When the reducing agent concentration is too high, the crystal structure of the catalyst is destroyed to a certain extent, resulting in a sharp decline in its performance.
[0080] Figure 15 The selectivity diagram of the catalytic reduction of low-concentration carbon dioxide to methane by the Co-MHOF photocatalyst in Example 1, the Hv-Co-MHOF-a photocatalyst in Example 2, and the Hv-Co-MHOF-b photocatalyst in Example 3 is shown. Figure 15 As can be seen, the Hv-Co-MHOF-a photocatalyst has the highest methane selectivity at 94.8%, while the Co-MHOF photocatalyst has a methane selectivity of 80.7% and the Hv-Co-MHOF-b has a methane selectivity of 83%. This is mainly due to the fact that adjusting the amount of sodium borohydride reducing agent modifies the electronic structure of the catalyst, changes the band gap width and the positions of the conduction and valence bands, thereby accelerating the separation efficiency of photogenerated electrons and holes and promoting the production of methane eight-electron products.
[0081] The embodiments described above are merely descriptions of preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Without departing from the spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by persons skilled in the art should fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing a photocatalyst for low-concentration CO2 reduction, characterized in that: The following steps are involved: A Co-MHOF precursor is prepared by a coprecipitation method using a cobalt source, an intercalation anion and an alkali source as raw materials; the Co-MHOF precursor is subjected to reduction etching by a reducing agent to obtain the photocatalyst; The method of reducing and etching the Co-MHOF precursor using a reducing agent comprises: mixing the Co-MHOF precursor, the reducing agent and water to obtain a mixed solution, stirring the mixed solution for reducing and etching, and centrifuging, washing and drying the mixed solution after the reducing and etching to obtain the photocatalyst; The reducing agent is sodium borohydride; the concentration of the reducing agent in the mixed solution is 0.01-1 mol·L -1 ; The reduction etching time is 10-60min; The cobalt source is an inorganic acid salt of cobalt, the alkali source is sodium hydroxide, and the intercalation anion is a salicylate ion.
2. The preparation method according to claim 1, characterized in that: The steps of preparing the Co-MHOF precursor by the coprecipitation method include: adding a cobalt inorganic acid salt solution to a salicylate ion solution under stirring conditions to obtain a mixed solution; dropping a sodium hydroxide solution into the mixed solution, heating the mixed solution for aging after the dropping is completed, and centrifuging, washing, and drying after the aging is completed to obtain the Co-MHOF precursor.
3. The preparation method according to claim 2, characterized in that: The concentration of the cobalt inorganic acid salt solution is 0.01-1 mol·L -1 The concentration of the salicylate ion solution is 0.01-0.5 mol·L -1 .
4. The preparation method according to claim 2, characterized in that: In the process of dripping the sodium hydroxide solution into the mixed solution, the dripping speed is controlled so that the pH of the solution system is maintained in the range of 7.0-9.
0.
5. The preparation method according to claim 2, characterized in that: The aging temperature is 80-95° C. and the aging time is 16-24 hours.
6. A photocatalyst for low concentration CO2 reduction prepared according to the preparation method according to any one of claims 1 to 5.
7. Use of the photocatalyst according to claim 6 in the photocatalytic reduction of low-concentration CO2 to produce methane, characterized in that: The volume concentration of the low-concentration CO2 is 2-50%.
Citation Information
Patent Citations
One-dimensional magnetic metal / carbon nano-composite material and preparation method thereof
CN103440947A
Photocatalyst for carbon dioxide reduction reaction and preparation method thereof
CN115709070A